JANOSIK NA SPISZU: „RYTUAŁ ESTETYCZNY” A TOŻSAMOŚĆ REGIONALNA - Barański, Janusz (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The subject of the analysis is a self-taught sculptor’s artistic activity from Niedzica in Spisz, which forms a part of the narratives of regional policies of the last decade. It manifests art brut characteristics, remaining outside aesthetics and art history criteria, while having a function of the material attribute of the dispersed ritual of identity within the local community. This function is shared by other spheres of aesthetics – from architectural forms, to interior design and garden decorations, to elements of the old folklore (dress, music, dance). The meanings of the art works are constituted on the level of the meta-cultural practices of everyday life, whose important feature is the clash between Polishness and Slovakishness, globalization and the revitalization of locality, the idea of local minority/foreign elites and the views of most residents.